Exploring the Role of AI Chatbot in English Language Teaching and Learning - Nasution, Maulana Oscard; Arianto, Arianto (Universitas Pahlawan Tuanku Tambusai, 2024)
The integration of Artificial Intelligence (AI) in education has garnered significant attention, with AI-Chatbots emerging as a transformative tool in English language teaching and learning. This investigation delves into the incorporation of AI-Chatbots in the context of English language instruction, with a specific focus on their capacity to enhance educational achievements. This researcher delves into various utilities of AI-Chatbots, elevating proficiency in English language, grammar, and vocabulary. The study employed a mixed methods strategy, amalgamating quantitative insights from teacher surveys with the interpretation of qualitative data. This study evaluates the efficacy of teachers utilizing AI-Chatbots with their students. The outcomes demonstrate that the teacher's involvement in furnishing guidance on the utilization of AI-Chatbots to students substantially heightens student engagement and motivation towards enhancing their English language competencies. Subsequent research endeavors should concentrate on enhancing the contextual comprehension capabilities of Chatbots and investigating their amalgamation with other educational technologies.